2022
DOI: 10.3390/w14152441
|View full text |Cite
|
Sign up to set email alerts
|

Hydro-Geochemistry and Groundwater Quality Assessment of Ouargla Basin, South of Algeria

Abstract: This study aims to evaluate the hydro-chemical characteristics of Ouargla, Algeria basin groundwaters harvested from the Mio Pliocene aquifer. The study covered 70 samples; the physical parameters, potential of hydrogen (pH), and electrical conductivity EC μS.cm−1 were determined in situ, using a multiparameter; the laboratory analysis included dry residuals DR (mg/L), calcium Ca2+ (mg/L), magnesium Mg2+ (mg/L), sodium Na+ (mg/L), potassium K+ (mg/L), bicarbonates HCO3− (mg/L), sulfates SO42− (mg/L), and chlor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 26 publications
0
2
1
Order By: Relevance
“…Some observe that the guide value (400 mg l −1 ) prescribed by Algerian Standards ( 2011) is met for all samples, except for No.14,No.19,No.24,No.26 and No.39. These sulfate values are significantly higher than those obtained in the study conducted by Mansouri et al (2022) in the Ouargla Basin, placed in the South of Algeria, where sulfate values ranged from 476.00 to 2290 mg l −1 . For anions, the mean concentration follows a descending order as SO −2 4 > HCO − 3 > Cl − > NO − 3 , being their concentrations 305.3, 232.3, 181.3, and 26.5 mg l −1 , respectively.…”
Section: Discussioncontrasting
confidence: 72%
“…Some observe that the guide value (400 mg l −1 ) prescribed by Algerian Standards ( 2011) is met for all samples, except for No.14,No.19,No.24,No.26 and No.39. These sulfate values are significantly higher than those obtained in the study conducted by Mansouri et al (2022) in the Ouargla Basin, placed in the South of Algeria, where sulfate values ranged from 476.00 to 2290 mg l −1 . For anions, the mean concentration follows a descending order as SO −2 4 > HCO − 3 > Cl − > NO − 3 , being their concentrations 305.3, 232.3, 181.3, and 26.5 mg l −1 , respectively.…”
Section: Discussioncontrasting
confidence: 72%
“…Pyrite is a mineral that can be found in rocks of any nature and geological age, but especially in metamorphic and sedimentary rocks, and is often associated with clay beds. The presence of sulphate ions in borehole water is mainly related to the dissolution of gypsum formations [28,29]. Nonetheless, Porowski et al [30] reported that favourable conditions can lead to the oxidation of pyrite or aqueous sulphides and result in the formation of sulphate ions (Equations ( 5) and ( 6)):…”
Section: Characteristics Of the Water From The Boreholementioning
confidence: 99%
“…Water quality assessments can provide detailed information on the underground geological conditions where the water occurs [1]. Numerous studies have been conducted around the world to evaluate the geochemistry of groundwater [4][5][6][7][8][9]. Studies on the quality of groundwater have also been done in India [10,11].…”
Section: Introductionmentioning
confidence: 99%